Caracterización morfo-anatómica y protocolo para estimar la viabilidad de semillas de Psidium guajava - Guevara Ohara, Jorge Ernesto; Cardozo Conde, Carlos Iván; Santos Meléndez, Luís Guillermo (Universidad Nacional de Colombia, 2020)
Most research on P. guajava has been oriented to analyze nutritional composition of the fruits and some are related to the use of pre-germinative treatments for the release of seed dormancy in some genetic materials. However, no protocols have been developed that allow the determination of the viability of the seed; by using tetrazolium as an indicator. For the morpho-anatomical characterization of the P. guajava seed, four varieties of great economic importance for the CORPOICA Germplasm Bank were analyzed (Palmira ICA I, Cimpa Pulpa Roja, Manzana and Cl-0440A). A factorial test was performed to determine the concentration of Tetrazolium, exposure time and temperature effects. Guava seeds have a hard consistency testa, which is not an impediment to the imbibition process. The seed exhibits different forms (oboved, dentate, nailed, oblong, ovoid and reniform). The embryo is peripheral and has its fully developed structures at the time of seed extraction of fruits that have physiological maturity. The diameters, thickness and unit weight (g/100 seeds) of the guava seed vary according to the variety, which is probably related to the number of seeds contained in each fruit. The knowledge of the concentration and exposure time of the seeds to the Tetrazolium is of paramount importance for the evaluation of the physiological quality of the seed. A concentration of 0.1% for 12 hours of exposure under temperature conditions 26 ± 2 ° C and 40% relative humidity and 1% for 3 hours of exposure under controlled temperature conditions 40 ° C allows unambiguous assessment of physiology quality of the seed of this species.